2010
DOI: 10.1111/j.1442-2050.2009.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of psychopathological changes on quality of life after laparoscopic fundoplication for the treatment of gastroesophageal reflux

Abstract: There are references in medical literature to the influence of psychopathological changes and their negative impact on the results of laparoscopic fundoplication. The objective of this study is to analyze the influence of psychological changes, as assessed by the General Health Questionnaire-28 (GHQ-28), on patients undergoing surgery for gastroesophageal reflux. This is a prospective study in a series of 103 consecutive patients (62 males and 41 females with a mean age of 40 years) undergoing laparoscopic fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The correlation between patients’ satisfaction and postoperative QoL scores is a point of controversy in the literature. Good concordances with QoL questionnaires or essential parts of it are described as well as a lack of correlation [25,26,29]. Furthermore, a most recent prospective observational study showed that females were less satisfied with the outcome after fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between patients’ satisfaction and postoperative QoL scores is a point of controversy in the literature. Good concordances with QoL questionnaires or essential parts of it are described as well as a lack of correlation [25,26,29]. Furthermore, a most recent prospective observational study showed that females were less satisfied with the outcome after fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…15 Evidence in the literature also suggests that psychosocial and psychopathological patient characteristics can influence patient satisfaction and perceived quality of life after gastrointestinal surgery regardless of clinical outcome. 16 The healthrelated quality of life of pediatric patients after laparoscopic cholecystectomy has not yet been examined. For these reasons, we selected the CHQ-PF28, which is a valid and reliable tool to measure psychosocial and general health in children, and a modified GIQLI to examine gastrointestinal symptoms and gastrointestinal-related quality of life.…”
Section: Discussionmentioning
confidence: 99%